2018
DOI: 10.5009/gnl18221
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 17beta;-Estradiol on Colonic Permeability and Inflammation in an Azoxymethane/Dextran Sulfate Sodium-Induced Colitis Mouse Model

Abstract: Background/AimsIntestinal barrier dysfunction is a hallmark of inflammatory bowel diseases (IBDs) such as ulcerative colitis. This dysfunction is caused by increased permeability and the loss of tight junctions in intestinal epithelial cells. The aim of this study was to investigate whether estradiol treatment reduces colonic permeability, tight junction disruption, and inflammation in an azoxymethane (AOM)/dextran sodium sulfate (DSS) colon cancer mouse model.MethodsThe effects of 17β-estradiol (E2) were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 63 publications
(67 reference statements)
0
27
1
Order By: Relevance
“…26) Conversely, although estradiol improved the behavior of anxiety and depression in postmenopausal animal models, but it did not increase the expression of BDNF in the brain. 27) In addition, they compared the administration methods via subcutaneous (SC) and intracerebroventricular (ICV) route to examine therapeutic effect of estrogen on anxiety and depressive phenotypes in the postmenopausal mice model. In the study, ICV administration of estradiol shows a significant increase in the number of crosses into the central area but not SC, implying that depending on the concentration of estrogen that reaches the brain, the results of behavioral testing may vary.…”
Section: Discussionmentioning
confidence: 99%
“…26) Conversely, although estradiol improved the behavior of anxiety and depression in postmenopausal animal models, but it did not increase the expression of BDNF in the brain. 27) In addition, they compared the administration methods via subcutaneous (SC) and intracerebroventricular (ICV) route to examine therapeutic effect of estrogen on anxiety and depressive phenotypes in the postmenopausal mice model. In the study, ICV administration of estradiol shows a significant increase in the number of crosses into the central area but not SC, implying that depending on the concentration of estrogen that reaches the brain, the results of behavioral testing may vary.…”
Section: Discussionmentioning
confidence: 99%
“…[ 29 ] The absorption of drugs was affected by the pathological changes in gastrointestinal tract, the main place for drug absorption. In the case of intestinal mucosal damage, the expression of tight junction proteins between cells was reduced, and intestinal permeability was increased, [ 30 ] which could facilitate the penetration of material. The increasing evidence suggested that a dysregulation of the protease/antiprotease balance in the gut contributed to epithelial damage and increases permeability.…”
Section: Discussionmentioning
confidence: 99%
“…An automatic immunostainer (BenchMark XT; Ventana Medical Systems, Inc, Tucson, AZ, USA) and an UltraView Universal DAB detection kit (Ventana Medical Systems) were used for immunostaining. 22 Expression percentage was assessed as a ratio between the number of cells stained with ZO-1 divided by the total number of cells counted in a section. ZO-1 expression was quantified using ImageJ 1.50i software.…”
Section: Western Blot Analysis and Immunohistochemical Analysis Of Zomentioning
confidence: 99%